Analyzing competitive advantages on the basis of resource-based view: The concept of price and non-price factors - Maja Makovec Brenčič (Journal for East European Management Studies, 2001)
In the paper the author analyses the contemporary issues of gaining competitive advantages (CAs) at the firm level. The basic purpose of the paper is to develop theoretical and empirical analysis of non-price (invisible, intangible, non-traditional) factors (sources) of firm competitiveness. In author's opinion non-price factors present the base of vital importance for a successful firm performance nowadays. The paper introduces a research of the selected non-price factors (human resource, knowledge, innovation, quality, environment and location, time) in the Slovenian export manufacturing companies, which showed that the concept of price and non-price factors of CAs can be accepted as a contemporary mechanism of defining sources of CAs at firm level. – – Im folgenden Aufsatz werden gegenwärtige Ausgangspunkte für das Erzielen von Konkurrenzvorteilen durch Unternehmen analysiert. Das Ziel dieses Beitrages ist die Durchführung einer theoretischen und empirischen Analyse der nicht-preislichen (unsichtbaren, immateriellen, nicht traditionellen) Faktoren (Quellen) der Konkurrenzfähigkeit eines Unternehmens. Nach der Meinung der Autorin stellen die nicht-preislichen Faktoren heutzutage die wichtigste Grundlage für den erfolgreichen Geschäftsverkehr eines modernen Unternehmens dar. Der Aufsatz befasst sich im speziellen mit ausgewählten nicht-preislichen Faktoren (Menschenquellen, Kenntnisse, Innovationen, Qualität, Umwelt und Standort, Zeit) in slowenischen Exportverarbeitungsunternehmen. Im Ergebnis wird aufgezeigt, dass das Konzept der nichtpreislichen und preislichen Faktoren der Konkurrenzvorteile einen geeigneten und sinnvollen Mechanismus für das Definieren von Quellen für Konkurrenzvorteile auf Unternehmensniveau darstellt.
Keywords: 650